Differing impacts of cardiac implantable electronic device leads on tricuspid regurgitation - Sophie A. Leon; Melissa Austin; Nayeem Nasher; Daler Rahimov; Faizaan Siddique; Chitra Parikh; Danial Ahmad; Vakhtang Tchantchaleishvili; Behzad B. Pavri (Journal of Arrhythmia)
Abstract Background Placement of cardiac implantable electronic devices (CIED) with leads that traverse the tricuspid valve is thought to contribute to tricuspid regurgitation (TR). However, there are relatively limited data comparing the impact of different CIED lead types on the incidence and progression of TR. This study sought to quantify the change in TR severity following implantation of CIEDs with different lead types. Methods Patient data were collected on individuals with implantable cardioverter defibrillators (ICD), right ventricular‐paced pacemakers (RV‐PM), and His bundle‐paced pacemakers (His‐PM) placed by a single provider at a single institution between 2016 and 2019. Patients with extravascular CIED placement or with existing devices undergoing upgrade procedures were excluded. Severity of TR after CIED implantation was compared to baseline TR. Results A total of 97 patients receiving CIEDs were analyzed, including 63 with RV‐PMs, 23 with ICDs, and 11 with His‐PMs. Median patient age was 72 [interquartile range (IQR) 63–81] years, and 44% of patients were female. Echocardiograms were obtained a median of 20 [4–91] days before CIED implantation and 31 [17.9–43.0] months following implantation. Baseline TR grade was comparable between groups (p = 0.65). TR severity significantly worsened after ICD implantation (p = 0.035), RV‐PM implantation trended toward worsening TR severity (p = 0.099), and no statistically significant difference was observed after His‐PM implantation (p = 0.68). Conclusion The effect of CIED leads on TR represents a spectrum related to the type of lead traversing the tricuspid valve.